Visitor Restriction Policies and Practices in Children's Hospitals: Results of an Emerging Infections Network Survey. (4th October 2017) - Pong, Alice; Faltamo, Mekleet M; Beekmann, Susan E; Polgreen, Philip M; Shane, Andi L
Abstract: Background: Balancing the prevention of infections in pediatric healthcare settings with family-centered care is challenging. Visitor restriction policies (VRP) are difficult to implement and enforce. The purpose of this study was to delineate the timing, indications for, and assessment of VRP in pediatric facilities. Methods: The Infectious Diseases Society of America Emerging Infections Network surveyed 334 pediatric infectious disease consultants via an electronic survey. Descriptive analyses were performed. Results: One hundred and seventy (51%) of eligible respondents completed a survey between 12 July and 15 August 2016. Of these, 44 (27%) reported not knowing if their facility had a VRP and 17 (10%) reported having a policy but were unfamiliar with details; both groups were excluded from further analyses. 104 (61%) reported being somewhat familiar with the details of their VRP and 92 (88%) had a VRP in all inpatient units. Age-based VRP were reported by 77/104 (74%), symptom-based by 101 (97%), and outbreak-specific by 78 (75%). VRP were also implemented in the emergency department by 5 (5%), outpatient clinic by 9 (9%), day surgery by 6 (6%), or radiology by 3 (3%). Symptom-based VRP were seasonal in 24 (24%) of facilities, with 71 (70%) implemented year-round. Communication of VRP to families occurred at admission at 89 (87%) and through signage in care areas by 65 (64%). Communication of VRP to staff occurred by email for 79 (77%), by meetings for 56 (55%) and by signage in staff only areas for 50 (49%). Enforcement was the responsibility of nursing (82, 80%), registration clerks (59, 58%), unit clerks (54, 53%), the infection prevention team (32, 31%), or clinicians (16, 16%). The effectiveness of VRP was assessed by 63 (62%) through active surveillance of hospital acquired respiratory infections; 29 (28%) used active surveillance of healthcare worker exposures and 30 (29%) used patient/family satisfaction. Conclusion: VRP vary in scope, implementation, enforcement, and physician awareness in pediatric facilities. A prospective multisite evaluation of outcomes would facilitate the adoption of uniform guidance. Disclosures: All authors: No reported disclosures.